The slight spin of the old stellar halo - Deason, Alis J.; Grand, Robert J. J.; Pakmor, Rüdiger (Arxiv, 2017)
We combine Gaia data release 1 astrometry with Sloan Digital Sky Survey (SDSS) images taken some ~10-15 years earlier, to measure proper motions of stars in the halo of our Galaxy. The SDSS-Gaia proper motions have typical statistical errors of 2 mas/yr down to r ~ 20 mag, and are robust to variations with magnitude and colour. Armed with this exquisite set of halo proper motions, we identify RR Lyrae, blue horizontal branch (BHB), and K giant stars in the halo, and measure their net rotation with respect to the Galactic disc. We find evidence for a gently rotating prograde signal (< $V_φ$ > ~ 5-25 km/s) in the halo stars, which shows little variation with Galactocentric radius out to 50 kpc. The average rotation signal for the three populations is < $V_φ$ > = 14 +/- 2 +/- 10 (syst.) km/s. There is also tentative evidence for a kinematic correlation with metallicity, whereby the metal richer BHB and K giant stars have slightly stronger prograde rotation than the metal poorer stars. Using the Auriga simulation suite we find that the old (T >10 Gyr) stars in the simulated halos exhibit mild prograde rotation, with little dependence on radius or metallicity, in general agreement with the observations. The weak halo rotation suggests that the Milky Way has a minor in situ halo component, and has undergone a relatively quiet accretion history.
Gesehen am 15.02.2019